How Workload, Compensation and Work Stress Influence on the Performance of PT Airo Maha Kerinci’s Employees - Masruroh Masruroh; Charles Charles (Indonesia Banking School, 2020)
The purpose of this study was to determine the effect of workload, compensation, work stress on employee performance. The object of research is all employees of PT. Airo Maha Kerinci. Data collection techniques by distributing questionnaires to all employees of PT. Airo Maha Kerinci as many as 110 respondents and direct observation to the company. Method of data analysis using simple linear regression analysis and multiple linear regression analysis using IBM SPSS 22. The results showed that the workload has a nega-tive and significant effect on employee performance, compensation has a positive and significant effect on employee performance, while work stress has a negative and significant effect on employee performance. However, simultaneously workload, compensation, and work stress affect employee performance. The im-plications of the result are work load and work stress need to be improved so that passion for work and en-joyment of work are maintained amidst high workload.